2018
DOI: 10.1111/ssm.12306
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ views on and preferences for meeting their professional development needs in STEM

Abstract: While much is known about the characteristics that researchers deem valuable for professional development (PD), teachers' perceptions of their PD needs are less understood. In this study, we sought to explore teachers' perceptions of their PD needs, including PD format, time frame, and topics covered, and how those perceptions varied by teachers' district size, grade level, subject area, and years of experience.Participants included a statewide representative sample of 800 elementary and secondary STEM teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…The inductive thematic network analysis of the first-round questionnaire resulted in seven themes that showcase the various goals of PDPs. All of the emerging themes from the first round of our study had already been identified in previous studies (Borko, 2004;Hardy et al, 2010;Louws et al, 2018;Owens et al, 2018;Park Rogers et al, 2010), though not necessarily by all stakeholders. The themes were clustered into the three categories of professional knowledge: PK, CK, and PCK (Abell, 2007;Chan & Hume, 2019;Park & Oliver, 2008).…”
Section: Round 1: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The inductive thematic network analysis of the first-round questionnaire resulted in seven themes that showcase the various goals of PDPs. All of the emerging themes from the first round of our study had already been identified in previous studies (Borko, 2004;Hardy et al, 2010;Louws et al, 2018;Owens et al, 2018;Park Rogers et al, 2010), though not necessarily by all stakeholders. The themes were clustered into the three categories of professional knowledge: PK, CK, and PCK (Abell, 2007;Chan & Hume, 2019;Park & Oliver, 2008).…”
Section: Round 1: Resultsmentioning
confidence: 64%
“…First, we present the results of several studies on the learning goals of teachers participating in professional development (e.g., Anderson & Mitchener, 1994;Borko, 2004;Louws et al, 2018;Park Rogers et al, 2010;Van Duzor, 2012). Here, teachers identified three learning goals for their professional development: (1) to enhance their CK (Anderson & Mitchener, 1994;Louws et al, 2018;Owens et al, 2018;Park Rogers et al, 2010;Van Duzor, 2012), (2) to enhance their PK (Louws et al, 2018;Park Rogers et al, 2010), and (3) to enhance their PCK. In the latter, teachers specified various components of PCK.…”
Section: Learning Goals For Pdpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps with targeted PD and supportive instructional materials, teachers could integrate engineering in a way that motivates learners and increases skills in critical thinking and problem solving as a team (Lachapelle & Cunningham, ). Owens, Sadler, Murakami, and Tsai () conducted a study with 800 elementary and secondary STEM teachers from a wide range of school districts in Missouri, a state that incorporates engineering design standards within their K‐12 science standards. In this study, these teachers completed a needs assessment related to PD and the results provided evidence that teachers were most interested in learning about problem‐based learning and real‐world issues when teaching STEM content.…”
Section: Background Literaturementioning
confidence: 99%